An Evaluation the Effect of Alcohol Presence in Mouth Washes on Force Degradation of Different Configurations of Elastomeric Chains - Abdullah, Noor N; Ghaib, Nihdal H (Journal of Baghdad College of Dentistry, 2016)
Background: Elastomeric chains are one of the most commonly used force delivery systems. They have the ability to exert a continuous force, convenience of use, compatibility to oral environment and cost effectiveness but one of the inherited disadvantages is force degradation. Materials and methods: This in vitro study was designed to evaluate the effect of alcohol presence in mouthwashes on force decay of different configurations of clear elastomeric chains from (Ortho Technology company) which are: closed , short and long under the effect of time at (Initial, 1, 2, 3 and 4 weeks) intervals with exposure to different chemical solutions. A total (540) modules of elastomeric chains of three different types (long, short and closed) transparent in color, with an initial length (19mm) and about 50% extension (29mm) were used for the study. These elastomeric chains divided in to four groups and exposed to different chemical solutions (Listerine Original alcoholic mouthwash, Listerine Zero alcohol mouth wash, Ethanol 26.9%, distilled water) twice daily for 60 seconds according to manufacturer instructions to measure the amount of force degradation in different time intervals. These elastomeric chains were incubated in covered glass containers at 37CËš for the entire testing period. Results: Statistical analysis showed that there was a highly significant difference in the mean percentage of force decay (Pâ‰¤ 0.001). For all chemical solutions the highest percentage of force decay occurs in Listerine Original Alcoholic mouth wash. Also in all chemical solutions closed elastomeric chains has the least percentage of force decay. While closed configuration have the highest percentage of force decay. Conclusion: We can conclude that alcoholic mouth wash(Listerine Original) causes increase force degradation of all types of elastomeric chains while alcohol free mouth wash (Listerine Zero) causes less force degradation of all types of elastomeric chains. Also closed configuration elastomeric chains have the least percentage of force decay than other configurations.